Coma and Brainstem Reflexes - Mert Akan (Galenos Yayinevi, 2023)
Brain death is the complete and irreversible loss of whole brain functions including brainstem. Brain death is a clinical diagnosis and a person who is diagnosed as brain-dead is considered as dead both medically and legally. The three essential findings in brain death are unresponsive deep coma, loss of all brainstem reflexes and absence of spontaneous respiration (apnea).